2020
DOI: 10.1038/s41598-020-62831-0
|View full text |Cite|
|
Sign up to set email alerts
|

Interplay of Calcium and Nitric Oxide in improvement of Growth and Arsenic-induced Toxicity in Mustard Seedlings

Abstract: In this study, Ca 2+ mediated no signalling was studied in response to metalloid (As) stress in Brassica seedlings. Arsenic toxicity strongly suppressed the growth (fresh weight, root and shoot length), photosynthetic pigments, Chl a fluorescence indices (Kinetic traits: F v , F m , F v /F o , F m /F o , ФP o or F v /F m , Ψ o , ФE o , PI ABS , Area and N and redox status (AsA/DHA and GSH/GSSG ratios) of the cell; whereas energy flux traits: ABS/RC, TR o /RC, ET o /RC and DI o /RC along with F o , F o /F v , F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 53 publications
2
10
0
3
Order By: Relevance
“…These findings suggest the regulatory role of Ca 2+ and NO in SA induced signaling. Our results are in accordance with the earlier findings of Tiwari et al (2018;2019a,b) and Singh et al (2018aSingh et al ( , 2020a in Nostoc muscorum and mustard seedlings, respectively.…”
Section: Sa Ca 2+ and No Recover Antioxidant System To Neutralize Ni 2+ -Induced Oxidative Stresssupporting
confidence: 93%
See 1 more Smart Citation
“…These findings suggest the regulatory role of Ca 2+ and NO in SA induced signaling. Our results are in accordance with the earlier findings of Tiwari et al (2018;2019a,b) and Singh et al (2018aSingh et al ( , 2020a in Nostoc muscorum and mustard seedlings, respectively.…”
Section: Sa Ca 2+ and No Recover Antioxidant System To Neutralize Ni 2+ -Induced Oxidative Stresssupporting
confidence: 93%
“…From earlier studies it has been cleared that Ca 2+ plays essential role in regulation of growth, and different physiological processes of plants like stabilizes membrane structures by bonding with phospholipid bilayer, declines ROS levels, enhances key antioxidant enzymes, improves RubisCO activity and CO 2 fixation (Singh et al, 2018a,b;Tiwari et al, 2019a;Verma et al, 2018;Singh et al, 2020a,b), being an essential part of catalytic site of water oxidation (Mn 4 Ca 1 O x Cl y ) of PSII, it helps in the assemblage of water oxidizing complex (OEC) and directly regulates the photosynthetic activity (Andréasson et al, 1995;Bartlett et al 2008;Najafpour et al, 2012;Kalaji et al, 2014;Singh et al, 2018b;Singh et al, 2020a) under stressful environment. NO is also known for improvement in growth by regulating different physiological events like growth, photosynthetic pigments, photosynthetic activities, antioxidants defence system and reduces ROS levels produced by metals/ metalloids either by gene expression through signaling in a molecular cascade or by neutralizing excessive ROS through its free radical functioning (Zhang et al, 2008;Peto 2011;Chen et al, 2013;Xu et al, 2013;Sun et al, 2018;Tiwari et al, 2018;Singh et al, 2020a;Verma et al, 2020). According to a report, NO alleviate salinity stress by promoting photosynthetic rate in eggplant either by improving PSII quantum yield or by splitting excess energy via improving antenna molecules and carotenoid content (Wu et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…While PTIO reversed the Ca 2+ mediated betterment of defensive process even in the presence of SNP. Similar to this, Singh et al [ 77 ] have also demonstrated the interactive signaling role of Ca 2+ and NO in up-regulation of antioxidant defense machinery and thereby reduction of ROS accumulation inside the cells of mustard plant, leading to arsenic toxicity alleviation (see Fig. 7 ).…”
Section: Discussionsupporting
confidence: 59%
“…Previous studies have revealed that NO contributes to various aspects of stress tolerances by influencing ROS metabolism [ 9 ]. Ca 2+ -mediated NO signal transduction is involved in the response of Brassica seedlings to metalloid stress [ 10 ], and in Prunus persica (L.) Batsch, treatment with a NO solution can protect the fruit from pathogen infection by inducing the activity of defense enzymes and the expression of pathogenesis-related genes [ 11 ]. In two ecotypes of reeds, NO significantly reduces the contents of hydrogen peroxide (H 2 O 2 ) and malondialdehyde in calli and significantly inhibits the increase in ion leakage and growth inhibition and decrease in cell viability induced by HS [ 12 ].…”
Section: Introductionmentioning
confidence: 99%